Technical and Technological Analysis of the Novoilyinka Culture Ceramics of the Kama-Vyatka Interfluve - Olga V. Andreeva (Археология евразийских степей)
The article presents the results of technical and technological analysis of the Novoilyinsky culture ceramics of the Kama-Vyatka interfluve campsites: Arkul, Sredneye Shadbegovo I, Sredneye Shadbegovo II, Sredneye Shadbegovo III, Sredneye Shadbegovo IV. The main attention is paid to the preparatory stage of creating ceramic wares and surface treatment of finished vessels. When processing the outer surface of the wares of the studied sites, smoothing and polishing were used, but at the Arkul and Sredneye Shadbegovo III sites, vessels with a combed stamp on the outside of the vessel were revealed, the inner surface was mainly smoothed with a soft object. On the basis of the carried out technical and technological analysis the prevailing tradition of selection as an initial plastic raw material of non-sanded silty clay stands out, an insignificant percentage of wares was made of clay. Grog and an organic mortar were used to create the molding mass. The main recipe for creating Novoilyinka ceramics is: IPRM + organic mortar + grog in small concentration (1:7-1:5), not calibrated from 2,0 to 5,0 mm. The tradition of selecting non-sanded silty clay and adding grog and organic solution to the paste is stable for the Novoilyinka population and is inherited from the Kama culture.